Exponential Outer Synchronization between Two Uncertain Time-Varying Complex Networks with Nonlinear Coupling - Yongqing Wu; Li Liu (Entropy, 2015)
This paper studies the problem of exponential outer synchronization between two uncertain nonlinearly coupled complex networks with time delays. In order to synchronize uncertain complex networks, an adaptive control scheme is designed based on the Lyapunov stability theorem. Simultaneously, the unknown system parameters of uncertain complex networks are identified when exponential outer synchronization occurs. Finally, numerical examples are provided to demonstrate the feasibility and effectiveness of the theoretical results.